An Analysis of Online Learning in Academic Writing Course During the Covid-19 Pandemic at the Fourth Semester Students of English Language Education of FKIP UIR - Lisa Novi Riski; Arimuliani Ahmad (Universitas Pahlawan Tuanku Tambusai, 2021)
The abolition of in-person teaching and learning activities policy at universities due to the Covid-19 pandemic has resulted in a rapid transition from offline to online teaching and learning process. The inequality of internet networks in Indonesia makes this a challenge for lecturers and students. Academic Writing is also admitted by students as hard material. Hence, this study aims to analyze how the implementation of online learning in the Academic Writing course at the English Department of FKIP UIR. The instruments were an online questionnaire and structured interviews for students and the lecturer. The findings of this study found that the implementation of online learning in the Academic Writing course was held synchronously and asynchronously. Various online platforms support the teaching and learning process. However, many students have struggled with bad internet connections, were enabled to focus during the study, and have difficulty understanding materials.